Taking the Software Technology Major in Higher Vocational Education as an Example, Exploring the Path of Constructing Course Ideological and Political Demonstration Majors - Luo, Xinghua (Journal of Theory and Practice of Contemporary Education, 2023)
Due to its inherent advantages in cultivating students' correct values and professional views, the ideological and political curriculum has gradually been widely applied in teaching in vocational colleges. In this development context, many software technology teachers have begun to explore the path of constructing curriculum ideological and political demonstration majors based on professional teaching needs and students' overall learning situation, in order to achieve effective integration of curriculum ideological and political education and software technology majors, improve students' learning efficiency and quality, and ensure their healthy development. The article discusses and analyzes the significance and path of the construction of ideological and political demonstration majors in higher vocational software technology courses.